Synthesis and catalytic, antimicrobial and cytotoxicity evaluation of gold and silver nanoparticles using biodegradable, Π-conjugated polyamic acid. Issue 5 (7th September 2015) - Kariuki, Victor M.; Yazgan, Idris; Akgul, Ali; Kowal, Andrzej; Parlinska, Magdalena; Sadik, Omowunmi A.
Abstract : We hereby report a rapid and simple synthesis of silver (AgNPs) and gold nanoparticles (AuNPs) using conductive, electroactive and biodegradable poly(amic)acid (PAA) polymer as both the reductant and stabilizer. Abstract : We hereby report a rapid, simple, and one pot synthesis of silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) using conductive, electroactive and biodegradable poly(amic)acid (PAA) polymer as both the reductant and the stabilizer. The synthesized AgNPs and AuNPs were characterized using transmission electron microscopy (TEM), high-resolution TEM (HRTEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD) and ultraviolet-visible (UV-vis) spectroscopy. UV-vis spectra exhibit major peaks at 440 and 535 nm for AgNPs and AuNPs, respectively. The XRD patterns revealed four diffraction peaks at 38.12°, 44.07°, 64.27°, and 77.22° that can be indexed to the (111), (200), (220), and (311) planes of face-centered cubic (fcc) silver crystallites, respectively. The size of the crystallites along the [111] direction was estimated to be 4.2 ± 0.5 nm, which is in agreement with the TEM result. The effect of temperature on the formation of AgNPs in the presence of PAA was investigated and found to be significant at 100 °C, resulting in a silver–polyamic acid nanocomposite without altering the fcc crystal pattern. The prepared AuNPs and AgNPs were found to exhibit catalytic activity towards 4-nitrophenol and methylene blue with a rate constant of 5.2 × 10 −3 s −1 and 1.09 × 10 −2 s −1, respectively. Finally, the synthesized AgNPs exhibit excellent antibacterial activity against Gram negative ( E. coli DH5 Alpha, E. coli 25922, Aeromonas hydrophila and Pseudomonas aeruginosa ) and Gram positive ( Listeria monocytogenes strains F2365 and HCC7 and S. epidermidis ) bacteria in addition to modest cytotoxicity against non-cancerous immortalized IEC-6 and cancerous Caco-2 cell lines.